Introduction to Migration Studies An Interactive Guide to the Literatures on Migration and Diversity - Scholten, Peter (IMISCOE Research Series, 2022)
This open access textbook provides an introduction to theories, concepts and methodological approaches concerning various facets of migration and migration-related diversities. It starts with an introduction to migration studies and continues with an introductory reading of migration drivers, migration infrastructures, migration flows, and several transversal topics such as gender and migration. It also covers politics, policies and governance as well as specific research methods. As an interactive guide, this book develops an innovative format that brings a connection with various online sources. This means that whereas the chapters bring together literature in a coherent way, they are also connected to IMISCOE's online interactive Migration Research Hub for further reading and for more empirical material on migration and diversity. As such, this textbook provides a very useful introductory reading for undergraduate and graduate students as well as for policymakers, policy advisors, and all those interested in studies on migration and migration-related diversities.